Robot‐assisted Minimally‐invasive Internal Fixation of Pelvic Ring Injuries: A Single‐center Experience - Hua‐shui Liu (Orthopaedic Surgery, 2019)
Objective To investigate the indications, surgical strategy and techniques, safety, and efficacy of robot‐assisted minimally‐invasive internal fixation of pelvic ring injuries. Methods The clinical data of 86 patients with anterior and posterior pelvic ring injuries who underwent robot‐assisted minimally‐invasive internal fixation were retrospectively analyzed. The patients included 57 men and 29 women aged between 22 and 75 years, with an average age of (40.2 ± 13.6) years. According to the Tile classification, there were 5 (5.8%) type A2, 48 (55.8%) type B, and 33 (38.4%) type C fractures. The surgical plans were formulated based on the injury type of the pelvic ring, the effectiveness of the reduction, and the integrity of the osseous channel. Posterior pelvic ring injuries were treated with robot‐assisted percutaneous cannulated screw fixation of the sacroiliac joint. Anterior pelvic ring injuries were treated with robot‐assisted percutaneous cannulated screw fixation of the pubic ramus, INFIX fixation, or a “hybrid” fixation. The surgical complications and the efficacy of the surgical treatments were analyzed. Results A total of 274 screws were inserted with robotic assistance, of which 262 screws were successfully inserted to a satisfactory position on the first attempt. The number of screws placed per person was 3.2 on average, and the average operation time was 175 min (35–280 min). Fluoroscopies were performed an average of 29.1 times (range, 9–63 times), and it took 6.1 s to place each screw. There were 13 unsatisfactory guiding needle placements during the surgeries, among 7 of which cutting or penetration of the cortex was re‐planned until satisfactory insertions; 1 penetrated the pubic cortex, causing hemorrhage of the “crown of death,” and was changed to “hybrid surgery”. The robot‐assisted surgical wounds all healed by primary intention with satisfactory position and precision of screw insertions. All patients were followed up for 3–6 months, with an average of 4.2 months. There were two postoperative fixation failures, in which both patients had separated symphysis pubes after hybrid surgery. The average Majeed score at the last follow‐up was 92.4 points. Conclusions Robot‐assisted surgery is accurate and minimally invasive, with a high success rate for one‐time screw placement and satisfactory clinical results. The indications and surgical strategy should be rigorously selected, the level of surgical techniques mastered, and the operating procedures standardized, all of which may help to prevent surgical complications. Robot‐assisted surgery provides a novel modality for the minimally‐invasive treatment of pelvic ring injuries.